Spatio-temporal analysis of soybean cultivation in the municipality of Balsas - MA, Brazil (Research, Society and Development, 2023)
Studies of land use and occupation are important parameters for working on forest management and agricultural exploitation. In view of this, this work aimed to analyze the advance of the agricultural frontier of soybean cultivation and the main changes in land use and cover in the municipality of Balsas - MA in the period from 1990 to 2021. The municipality is located in the southern region of Maranhão and is part of the great national agricultural frontier, known as MATOPIBA, which comprises the Cerrado, Cerrado-Caatinga Transition and Amazon-Cerrado Transition biomes, in the states of Maranhão, Tocantins, Piauí and Bahia. Based on the mapping, it was observed that during the process of changing the use and cover of the land, there was a reduction in the area of Forest Formation, which was 76.67% (10,075.66 km²) in 1994 to 60.73% (7,895.76 km²) in 2021, with forest suppression of 2,179.89 km². Meanwhile, the Soy class saw an increase of 2,703.60 km² (19.65%), from a land use percentage of 0.93% in 1994 to 20.57% in 2021. Although the expansion of the soybean agricultural frontier has promoted positive economic impacts for the region, it is worth remembering that the advance of the agricultural frontier often involves the deforestation of areas of native vegetation, resulting in the loss of biodiversity, contributing to climate change and affecting local ecosystems. The use of remote sensing data in conjunction with the MapBiomas platform was effective, as it offers a comprehensive view of the patterns of expansion of the agricultural frontier, contributing to an understanding of environmental impacts and improving sustainable agricultural practices.